Resolving Psychological Conflicts: A Kurt Lewinian Analysis of Nina Riva in Taylor Jenkins Reid’s Malibu Rising - Hasanuddin, Andi Siti Fadhilah Namirah; Sunra, La; Nur, Riola Haya (Har Press Indonesia, 2025)
This study investigates how Nina Riva resolves her psychological conflicts in Taylor Jenkins Reid’s Malibu Rising by employing Kurt Lewin’s theory of Positive, Negative, and Induced Valence. The research aims to reveal how inner struggles and emotional tensions shape the protagonist’s transformation and self-realization. Using a qualitative descriptive method, the analysis focuses on the novel’s narrative structure, character interactions, and dialogues that illustrate the stages of Nina’s psychological development. The findings indicate that Nina predominantly resolves her internal conflicts through Positive and Positive Induced Valences, allowing her to attain emotional balance and personal growth. Negative valence also appears as an initial catalyst that triggers her self-awareness before she redirects it into constructive action. The study highlights that inner conflict in literature not only reflects human psychological processes but also functions as a narrative strategy to portray resilience, autonomy, and identity formation. This research contributes to the broader discussion of literary psychology by demonstrating how Lewin’s theoretical lens can deepen understanding of character motivation and emotional evolution in contemporary fiction.